2015
DOI: 10.5430/jbei.v2n2p57
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of reproducible vendor independent estimation of cardiac function based on first generation speckle tracking echocardiography

Abstract: Background: The clinical approval of speckle tracking echocardiography (STE) as an accepted measure of myocardial strain and of LV function is hindered by the discordance of the results among the vendors. Since echocardiography images are noisy, the measured displacements are smoothed or regularized, an operation affecting the strain results. We introduce an "Error-dependent weighted speckle tracking" (EWST) algorithm that allows sensitivity analysis to the different operations affecting noise and accuracy. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…almost no smoothing is applied. This is opposed to p=0.09 (an order of magnitude less), which has been shown in our previous publication [52] to affect the tracking procedure and the results, to disturb the uniform distribution of strain values along the myocardium and be less resilient to noise.…”
Section: A the K-sad Speckle Tracking Algorithmmentioning
confidence: 67%
See 1 more Smart Citation
“…almost no smoothing is applied. This is opposed to p=0.09 (an order of magnitude less), which has been shown in our previous publication [52] to affect the tracking procedure and the results, to disturb the uniform distribution of strain values along the myocardium and be less resilient to noise.…”
Section: A the K-sad Speckle Tracking Algorithmmentioning
confidence: 67%
“…for = 1, the minimally smoothed chain is a cubic spline interpolant. Based on our recent study [52], p is set here to be very high (0.9), i.e. almost no smoothing is applied.…”
Section: A the K-sad Speckle Tracking Algorithmmentioning
confidence: 99%
“…[11,12] Trache et al [12] have shown that limited image quality has a significant impact on the agreement between 3D and 2D numerical strain values, while Hoit, [11] has reported that measurement of strain rate (and strain) is influenced by image and signal quality, where a very high image quality is required to produce reasonable strain and strain rate results. In our previous publication, [13] we have shown that a typical block matching tracking algorithm that uses post tracking smoothness techniques to refine the resultant strain fields, is sensitive to the characteristics and amount of smoothing, as well as to the initial segmentation of the myocardial tissue and to the noise level. Consequently, any modification that is made to the post block-matching smoothing techniques may cause the (expected) inter-vendor strain differences.…”
Section: Introductionmentioning
confidence: 99%